2020
DOI: 10.1182/blood-2020-138924
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab in Primary CNS Lymphoma and Primary Testicular Lymphoma with CNS Involvement: Single Center Experience

Abstract: Background.Most patients with primary CNS lymphoma (PCNSL), an aggressive extranodal lymphoma confined to the CNS, have a poor prognosis in spite of development of chemotherapy regimens. First-line treatment consists of high-dose methotrexate-based (HD-MTX) regimen followed by consolidation with autologous stem cell transplantation or whole brain radiotherapy. Given that this tumor manifests predominantly in older patients with median age of 65 years, many patients are unable to tolerate intensive chemotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A high objective response rate was also reported in another monocentric retrospective study, including eight PCNSL patients treated with nivolumab. Three and four patients achieved a CR and a PR, respectively [59]. Unfortunately, these promising results have not been confirmed in a prospective study including 47 PCNSL and 19 patients with CNS relapse of primary testicular lymphoma (NCT02857426), according to the available results posted on clinicaltrials.gov in 2020.…”
Section: Immune Checkpoint Inhibitors (Ici)mentioning
confidence: 97%
“…A high objective response rate was also reported in another monocentric retrospective study, including eight PCNSL patients treated with nivolumab. Three and four patients achieved a CR and a PR, respectively [59]. Unfortunately, these promising results have not been confirmed in a prospective study including 47 PCNSL and 19 patients with CNS relapse of primary testicular lymphoma (NCT02857426), according to the available results posted on clinicaltrials.gov in 2020.…”
Section: Immune Checkpoint Inhibitors (Ici)mentioning
confidence: 97%
“…Reported responses in larger studies have been somewhat suboptimal yet remain encouraging in patients with very limited treatment options. 96,97 The current status of immunotherapy in PCNSL is nicely reviewed here. 98 Responses to chemotherapy are poor in the relapsed setting and toxicities are high, indicating that such therapies should only be offered after careful discussion of goals of care and consideration of palliative care or hospice therapy alone.…”
Section: Surveillance Postremission Therapymentioning
confidence: 99%
“…Owing to frequent copy number gains of 9p24.1/PD‐L1/PD‐L2 and additional translocations involving these loci, along with associated increases in tumour expression of PD‐L1/PD‐L2 in PCNSL, 10 ICIs have emerged as a potentially effective treatment. Earlier studies showed a good activity of ICIs whether used in monotherapy or in combination with rituximab to treat R/R PCNSL 11–15 . Nevertheless, a recent phase 2 trial of nivolumab in the R/R setting showed unsatisfactory results 16…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies showed a good activity of ICIs whether used in monotherapy or in combination with rituximab to treat R/R PCNSL. [11][12][13][14][15] Nevertheless, a recent phase 2 trial of nivolumab in the R/R setting showed unsatisfactory results. 16 Because of the variable efficacy of immune checkpoint blockade therapy (CBT), an investigation into relevant biomarkers in PCNSL is urgently needed.…”
Section: Introductionmentioning
confidence: 99%